Decoupling Analysis of Water Resources Utilization and Economic Development in Henan Province - SHEN Yujie (Renmin Zhujiang)
Based on the decoupling theory,this paper builds the Tapio decoupling index model of water resources utilization and economic development of Henan province in 2009—2018,and conducts decomposition analysis for main factors affecting the water resources utilization in Henan province by LMDI model,the results show that:In overall,the water resources utilization and economic development of Henan province are in a state of decoupling,indicating that there is a coordination between them,but the absolute decoupling is not achieved;From the perspective of industrial structure,the total decoupling elasticity is better than the industrial decoupling elasticity and the agricultural decoupling elasticity;Economic level is the most important positive influence factor of water resources utilization in Henan province,while both the industrial structure and the intensity of water utilization exert a negative impact.Therefore,it is necessary to adjust the industrial structure reasonably,improve the utilization efficiency of water resources and develop efficient ecological agriculture.